NIKAH SIRI DALAM PERSPEKTIF HUKUM PERKAWINAN NASIONAL - OKY DEVIANY BURHAMZAH (Universitas Bengkulu, 2016)
Abstract Marriage is one of the importants event in human lifes, particularly for moslem family. Bacause of its important, then marriage regulated not only on state laws, but in Al-quran as well. In Marriage Law in Section 1 of Article 1, mentioned that marriage is legal if conducted according to their religion and beliefs. Meanwhile in Section 2 of Article 2, mentioned that each marriage noted according to the applicable law. Based on that articles above, then marriage registration is not legality condition of marriage. Nikah Siri that conducted without registered, but according to the principles and condition of islamic marriage law. This is give rise to pro and contra in the society related to that legality of marriage.